Quality of life of people living with HIV/AIDS (PLWHIV) Receiving Antiretroviral Therapy (ART) / Rahayu Abd.Manan - Abd.Manan, Rahayu (2016)
Purpose: To provide information regarding the effect of antiretroviral treatment (ART) on the quality of life (QoL) of patients living with HIV (PLWHIV). Participants have been recruited among PLWHIV and under antiretroviral treatment from the Retroviral Disease (RVD) clinic during their appointment day at the Hospital Tengku Ampuan Rahimah Klang. This study is mainly aimed to characterize PLWHIV who has been treated with ART regiment for at least 3 months and assessing their quality of life using WHOQOL-HIV-BREF. The 31-questions assessment comprises of 2 general items that covers the overall quality of life and perception of health status. The assessment also includes 6 domains; which are physical, psychological, level of independence, social relationships, environment and spirituality. Methodology: This cross-sectional study evaluates the quality of life and its associated factors amongst people living with HIV/AIDS at Hospital Tengku Ampuan Rahimah Klang. The present study did not involve any intervention. The study was conducted for a period of three (3) months starting from September to November 2015 with a total of 152 of participants. The participants were conveniently selected from the RVD clinic at HTAR. The criteria for eligible participants were 18 years or older, willing to participate in the study, confirmed with a diagnosis of HIV/AIDS and receiving ART for at least 3 month, physically able to answer questions in the questionnaires and receiving treatment with care and support. Results: This cross- sectional study showed that the majority of subjects were male (67.1%), and 55.9 % of participants are educated up to the secondary level. Statistical analysis showed a significant association in certain aspects of socio-demographic and clinical status of PLWHIV receiving ART at Hospital Tengku Ampuan Rahimah Klang (HTAR) with QoL domains. There is a highly significant association between different level of CD4-T cell counts (<350 cells/mm³ or >350cells/mm³) and psychological, level of independences, social relationship, environment and spiritual domains. The p value < 0.05 and CI did not across 0. But there is no significant